Impact of co-occurring hearing and visual difficulties in childhood on educational outcomes: a longitudinal cohort study - Matilda Hill; Amanda Hall; Cathy Williams; Alan M Emond (BMJ Paediatrics Open)
Background Mild hearing and visual difficulties are common in childhood, and both may have implications for educational achievement. However, the impact of co-occurring common hearing and visual difficulties in childhood is not known.Objective To determine the prevalence and impact of co-occurring common hearing and visual difficulties of childhood on educational outcomes in primary and secondary school.Methods The sample was drawn from the Avon Longitudinal Study of Parents and Children, a longitudinal birth cohort study in England. The exposures were hearing and visual difficulties at age 7 (defined as conductive hearing loss or otitis media with effusion, and amblyopia, strabismus or reduced visual acuity, respectively). The outcomes measured were achievement of level 4 or above at Key Stage 2 (KS2) in English, Maths and Science, respectively, at age 11, and attainment of five or more General Certificate of Secondary Education (GCSEs) at grades A*–C at age 16. Multiple logistic regression models assessed the relationship between hearing and visual difficulties and educational outcomes, adjusting for potential confounding factors.Results 2909 children were included in the study; 261 had hearing difficulties, 189 had visual difficulties and 14 children had co-occurring hearing and visual difficulties. Children with co-occurring hearing and visual difficulties were less likely to achieve the national target at KS2 compared with children with normal hearing and vision, even after adjustment for confounding factors (OR 0.30, CI 0.15 to 0.61 for KS2 English). Differences in IQ, behaviour, attention and social cognition did not account for this relationship. The impact of co-occurring hearing and visual difficulties on GCSE results was explained largely by poor performance at KS2.Conclusions Co-occurring hearing and visual difficulties in childhood have an enduring negative impact on educational outcomes. Identification of affected children and early intervention in primary school is essential.